Movement away from feeding site of the aphid Sitobion αvenαe (F.) (Hemiptera: Aphididae) when parasitized by Aphelinus αbdominαlis (Dalman) (Hymenoptera: Aphelinidae) - Lykouressis D.Ρ.; Emden Η.F. Van (ENTOMOLOGIA HELLENICA, 1983)
The aphid Sitobion avenae (F.), parasitized by Aphelinus abdominalis (Dalman), tends to leave either the feeding sites gathering in particular parts of its host-plant or even the host-plant. This behavior partially explains the phenomenon of reduced parasitism contribution to the overall mortality in several aphid population studies as interpreted by Hughes’ method.